Stimulus-responsive assembly of nonviral nucleocapsids - Mao Hori; Angela Steinauer; Stephan Tetter; Jamiro Hälg; Eva-Maria Manz; Donald Hilvert (Nature Communications, 2024)
Abstract Controlled assembly of a protein shell around a viral genome is a key step in the life cycle of many viruses. Here we report a strategy for regulating the co-assembly of nonviral proteins and nucleic acids into highly ordered nucleocapsids in vitro. By fusing maltose binding protein to the subunits of NC-4, an engineered protein cage that encapsulates its own encoding mRNA, we successfully blocked spontaneous capsid assembly, allowing isolation of the individual monomers in soluble form. To initiate RNA-templated nucleocapsid formation, the steric block can be simply removed by selective proteolysis. Analyses by transmission and cryo-electron microscopy confirmed that the resulting assemblies are structurally identical to their RNA-containing counterparts produced in vivo. Enzymatically triggered cage formation broadens the range of RNA molecules that can be encapsulated by NC-4, provides unique opportunities to study the co-assembly of capsid and cargo, and could be useful for studying other nonviral and viral assemblies.